2011
DOI: 10.2139/ssrn.1992957
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Broadband Infrastructure on Entrepreneurial Activities: The Case of Germany

Abstract: Die Dis cus si on Pape rs die nen einer mög lichst schnel len Ver brei tung von neue ren For schungs arbei ten des ZEW. Die Bei trä ge lie gen in allei ni ger Ver ant wor tung der Auto ren und stel len nicht not wen di ger wei se die Mei nung des ZEW dar.Dis cus si on Papers are inten ded to make results of ZEW research prompt ly avai la ble to other eco no mists in order to encou ra ge dis cus si on and sug gesti ons for revi si ons. The aut hors are sole ly respon si ble for the con tents which do not neces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Places with large technological endowments, which include ICT infrastructure, contribute to the vitality of entrepreneurial and innovative activities. This is particularly the case for high-tech industries like software or knowledge-based services which intensely utilise technology (Heger et al 2011). Indeed, Henderson et al (2007) identified infrastructure as one of the five key factors driving regional entrepreneurship along with human capital, amenities, financial capital and the local economy.…”
Section: Introductionmentioning
confidence: 99%
“…Places with large technological endowments, which include ICT infrastructure, contribute to the vitality of entrepreneurial and innovative activities. This is particularly the case for high-tech industries like software or knowledge-based services which intensely utilise technology (Heger et al 2011). Indeed, Henderson et al (2007) identified infrastructure as one of the five key factors driving regional entrepreneurship along with human capital, amenities, financial capital and the local economy.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the use of ICT in a firm’s business operations reduces the importance of the firm’s plant location. For example, Heger et al (2011) argue that the development of ICT infrastructure reduces the necessity of physical proximity, as information and knowledge can be transmitted through the Internet, making physical proximity to knowledge ‘incubators’ dispensable. In addition, a residential Internet connection is a prerequisite for working at home and may allow for new work practices (Autor, 2000).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The impact of ICT development on venture creation, which is often considered the backbone of a sustainable and growing economy (Heger et al, 2011), has also drawn the attention of scholars. A number of studies argue that the development of ICT can promote and inspire entrepreneurship, leading to more venture creation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations